Surgical Strategies and Prognostic Factors in Invasive Bladder Cancer: A Systematic Review - T. Nirza Vardoeli; Neza Aulina (International Medical Journal Corp. Ltd, 2024)
Background: Invasive bladder cancer presents a substantial health challenge due to its aggressive nature and high incidence. Surgical management, primarily through open radical cystectomy (ORC), laparoscopic radical cystectomy (LRC), and robotic-assisted radical cystectomy (RARC), is essential in treating this malignancy. Understanding the comparative outcomes of these surgical approaches and identifying prognostic factors is crucial to optimize patient care. Methods: This systematic review synthesized data from studies meeting specific inclusion criteria focused on the outcomes of ORC, LRC, and RARC for invasive bladder cancer. Major databases, including Emerald, Science Direct, and Sagepub, were searched to collate relevant studies. Key aspects analyzed included perioperative outcomes, oncological results, and the influence of prognostic factors such as lymph node dissection and surgical margin status. Results: The review revealed that minimally invasive techniques, namely LRC and RARC, demonstrate comparable oncologic outcomes to ORC, with distinct advantages in perioperative recovery, including reduced blood loss and shorter hospital stays. Prognostic factors like extensive lymph node dissection and achieving negative surgical margins were associated with improved survival and recurrence rates. Conclusion: The findings support that the choice of surgical approach should be tailored based on patient-specific factors and institutional expertise to enhance outcomes. High-quality, individualized surgical care is paramount, emphasizing the role of centralizing bladder cancer surgeries to high-volume centers and establishing referral networks for optimal patient management.